Objektivisering - Koutsomichalis, Marinos (My University, 2017)
Objektivisering is an experimental system for the computational modeling of generative 3D-printable models. The system pivots on Natural Language Understanding technologies and big 3D data. It processes arbitrary text input, eventually generating an array of words and phrases that summarise its meaning. These are then used as queries to retrieve 3D data from Thingiverse. Finally, the resulting bag of models is concatenated, in this way producing original 3D-printable designs in a computational fashion. Albeit being concretely physical, the resulting artefacts also incorporate the cybernetic encodings of their own making. In this way, they celebrate a certain kind of objecthood which is hybrid, post-digital, and self-introspective at a structural level, in this way concretely accelerating materialist aesthetics.